DEVELOPING CRITICAL THINKING IN MEDICAL EDUCATION THROUGH THE TECHNOLOGIES OF BIOLOGICAL MODELLING - Atakhanov Sanjarbek Anvarovich; Sohibjonova Gullola (Bright Mind Publishing, 2025)
This article discusses the development and formation of critical thinking skills in medical students through the use of modern technologies, particularly biological modelling tools, in the medical education system. The role of modelling technologies in applying theoretical medical knowledge to practical situations, understanding complex biological processes, and developing scientifically-based approaches is analyzed. The author integrates this process with interactive, integrated, and analytical approaches to education, highlighting the intellectual foundations of critical thinking. Furthermore, the article examines practical examples, modelling programs used in lessons, and analyzes their effectiveness.
Keywords: Medical education, biological modelling, critical thinking, interactive technology, student engagement, scientific analysis, integrated approach.